ESTABLISHMENT OF REGULARITIES OF THE INFLUENCE OF FACTORS THAT DETERMINE THE ELECTROCHEMICAL STABILITY WINDOW OF AQUEOUS ELECTROLYTES FOR SODIUM-ION BATTERIES - Akatay, T.A.; Kurbatov, A.P.; Kohmetova, S.T. (National Laboratory Astana, 2022)
The use of water as a battery electrolyte provides better ion migration. Also, an aqueous electrolyte is more environmentally friendly and safe, the low price of such electrolytes is also important, in addition, water is an excellent solvent for many salts...
Keywords: Type of access: Embargo; sodium-ion batteries